2019
DOI: 10.1177/1082013219894202
|View full text |Cite
|
Sign up to set email alerts
|

Low-density polyethylene films incorporated with silver nanoparticles to promote antimicrobial efficiency in food packaging

Abstract: Technological innovations in packaging are intended to prevent microbiological contaminations for ensuring food safety and preservation. In this context, researchers have investigated the antimicrobial effect of low-density polyethylene films incorporated with the following concentrations of silver nanoparticles: 1.50, 3.75, 7.50, 15.00, 30.00, 60.00, and 75.00 µg/ml. The films were characterized using field emission gun scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…They highlighted that the PE based nanocomposite-packaging material eliminate the ethylene and control the carbon dioxide and oxygen level, which extended the shelf life of mushroom up to 14 days. Low-density polyethylene films contained silver nanoparticles inhibited the growth of fungi and gram negative bacteria (Costa Brito et al 2019). Nanocomposite based packaging is the best way to preserve the liquid foods (Manikantan et al 2017) and has the commercial potential (Donglu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They highlighted that the PE based nanocomposite-packaging material eliminate the ethylene and control the carbon dioxide and oxygen level, which extended the shelf life of mushroom up to 14 days. Low-density polyethylene films contained silver nanoparticles inhibited the growth of fungi and gram negative bacteria (Costa Brito et al 2019). Nanocomposite based packaging is the best way to preserve the liquid foods (Manikantan et al 2017) and has the commercial potential (Donglu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties and water vapor transmission rate of CS-gelatin films can be improved due to addition of AgNPs, while optical and oxygen permeability properties remained unchanged. These films had the ability to inhibit growth of E. coli, Pseudomonas aeruginosa, and B. cereus [58] Nanocomposite films based on CS-PVA and AgNPs CS-AgNPs have no cytotoxicity effect, which suggests the possibility of CS-AgNPs use in food packaging applications [59] AgNPs-silk/PVA film The prepared AgNPs-silk/PVA film showed excellent mechanical performance and stability, as well as good antibacterial activity against both Gram-negative and Gram-positive bacteria [60] PLA/ZnO:Cu/Ag bionanocomposite films PLA/ZnO:Cu/Ag bionanocomposites were promising materials for food packaging application [61] PVC films with AgNPs The composites with AgNPs exhibited better antimicrobial and antifungal activities compared to without AgNPs [62] LDPE/AgNPs films The proposed films were effective to inhibit E. coli [63] PVC-based films with AgNPs An improvement in the mechanical strength, antibacterial, and antioxidant properties of the films was observed [64] PE films incorporated with AgNPs The improved films exhibited antimicrobial properties against all tested microorganisms [65] CS/AgNPs/purple corn extract (PCE) films CS/AgNPs/purple corn extract (PCE) films showed antioxidant and antimicrobial properties [66] PHBV films with AgNPs The addition of AgNPs can lead to a significant reduction in the water vapor and oxygen permeability of the films the neat matrix. Moreover, the developed nanocomposites films showed a strong and prolonged antibacterial activity against all tested bacteria [67] AgNPs/PVA/BNC film prepared via the ultraviolet (UV) method showed higher antimicrobial activity than the reduction method.…”
Section: Food Packaging Materials Main Finding Referencementioning
confidence: 91%
“…Ascorbic acid content of fresh-cut carrots was also maintained ( Becaro et al, 2016 ). A recent study reported that LDPE/AgNP films had a greater effect on gram-negative bacteria and fungi than gram-positive bacteria ( Brito et al, 2020 ). Additional, antimicrobial properties of nanocomposites of carrageenan/AgNPs/Laponite was demonstrated against the both gram-negative E. coli and gram-positive S. aureus ( Vishnuvarthanan and Rajeswari, 2019 ).…”
Section: Antimicrobial Nanopackagingmentioning
confidence: 99%